KRIVET 15th Anniversary International Seminar : youth employability and skills development - (:unkn) unknown (My University, 2012)
International representatives of VET met on October 9, 2012, in Seoul on the occasion of the 15th anniversary of KRIVET, BIBB's Corean counterpart. The participants of the international seminar discussed in two sessions the general topic "Youth Employability and Skills Development", which is a major policy challenge for many countries around the world. In the first session of the conference, examples from European countries (Germany, United Kingdom) and the United States were presented. The second session dealt with the situation in Asian countries (Taiwan, Japan, China, Korea). (BIBB-Doku)
Keywords: G 1.2.2.4 Arbeitslosigkeit; S System beruflicher Bildung; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; I 2.3.4 Asien; Jugendarbeitslosigkeit; Beschäftigungsfähigkeit; Berufsbildung; Beziehung Bildungssystem Beschäftigungssystem; Bundesrepublik Deutschland; Vereinigtes Königreich; USA; Taiwan; Japan; China; Südkorea